Reduced prothrombinase inhibition by tissue factor pathway inhibitor contributes to the factor V Leiden hypercoagulable state - Wood, J.; Kreuziger, L.; Ellery, Paul; Maroney, S.; Mast, A. (AMER SOC HEMATOLOGY, 2017)
Activated factor V (FVa) and factor X (FXa) form prothrombinase, which converts prothrombin to thrombin. The a isoform of tissue factor (TF) pathway inhibitor (TFPI) dampens early procoagulant events, partly by interacting with FV. FV Leiden (FVL) is the most common genetic thrombophilia in Caucasians. Thrombosis risk is particularly elevated in women with FVL taking oral contraceptives, which produce acquired TFPIa deficiency. In mice, FVL combined with 50% reduction in TFPI causes severe thrombosis and perinatal lethality. However, a possible interaction between FVL and TFPIa has not been defined in humans. Here, we examined this interaction using samples from patients with FVL in thrombin generation and fibrin formation assays. In dilute TF- or FXa-initiated reactions, these studies exposed a TFPI-dependent activation threshold for coagulation initiation that was greatly reduced by FVL. The reduced threshold was progressively overcome with higher concentrations of TF or FXa. Plasma assays using anti-TFPI antibodies or a TFPI peptide that binds and inhibits FVa demonstrated that the decreased activation threshold resulted from reduced TFPIa inhibition of prothrombinase. In assays using purified proteins, TFPIa was a 1.7-fold weaker inhibitor of prothrombinase assembled with FVL than with FV. Thus, FVL reduces the threshold for initiating coagulation, and this threshold is further reduced in situations of low TFPIa concentration. Individuals with FVL are likely prone to thrombosis in response to weak procoagulant stimuli that would not initiate blood clot formation in individuals with FV.